Overview of the Commemorations of the Bicentenary of the French Invasions - Fernanda Paula Maia (2015)
The commemorations of the French invasions in Portugal continued until the end of September 2010, this being the date that marked two hundred years since the Battle of Buçaco. These commemorations did not yet mark the date of the definitive withdrawal of the invading forces from Portuguese territory, which was only to happen in early April 1811, when, under the command of Massena, the French troops, already having been defeated and confronted with the defensive complex formed by the lines of Torres Vedras that barred their advance upon Lisbon, crossed over the border from Portugal to Spain, bringing an end to what was to become known as the 3rd French Invasion.